Emerging trends in DNA and RNA methylation modifications in type 2 diabetes mellitus: a bibliometric and visual analysis from 1992 to 2022 - Jiang, Cai; Hu, Yue; Wang, Sinuo; Chen, Cong (Frontiers in Endocrinology, 2023)
Background: Type 2 diabetes mellitus (T2DM) is a pathological metabolic disorder induced by the interaction of genetic and environmental factors. Epigenetic modifications, especially DNA and RNA methylation, might be the bridge between hereditary and environmental factors. This study aimed to comprehensively analyze the current status and prospective trends on the association between T2DM and DNA/RNA methylation modifications by using bibliometric software. Methods: All the publications in the Web of Science database for the research of T2DM with DNA and RNA methylation modifications were obtained from the earliest mention to December 2022. CiteSpace software was used to analyze the countries, institutions, journals/cited-references, authors/cited-authors and keywords. Results of the comprehensive visualization and bibliometric analysis were displayed relative to the research hotspots and knowledge structure. Results: A total of 1233 publications related to DNA and RNA methylation modifications and T2DM were collected. The number of publications per year and the overall trend consistently and significantly increased during the investigation period. Based on the highest publication counts, the major influential country was the USA, while Lund University was the most productive institution. DIABETES was considered as the most popular journal. The most frequent keywords identified in the field of methylation and T2DM were mainly involved in developmental origin, insulin resistance and metabolism. The study suggested that the study of methylation modifications had an increasingly significant role in understanding the progression of T2DM. Conclusion: CiteSpace visualization software was utilized to investigate the status and trends of DNA and RNA methylation modifications in the pathology of T2DM over the past 30 years. Findings from the study provide a guiding perspective for researchers regarding future research directions in this field.